2012
DOI: 10.1126/science.1224221
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Colloidal Superparticles from Nanorods

Abstract: Colloidal superparticles are nanoparticle assemblies in the form of colloidal particles. The assembly of nanoscopic objects into mesoscopic or macroscopic complex architectures allows bottom-up fabrication of functional materials. We report that the self-assembly of cadmium selenide-cadmium sulfide (CdSe-CdS) core-shell semiconductor nanorods, mediated by shape and structural anisotropy, produces mesoscopic colloidal superparticles having multiple well-defined supercrystalline domains. Moreover, functionality-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
369
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(374 citation statements)
references
References 28 publications
2
369
0
3
Order By: Relevance
“…Such binary nanoparticle superstructures have been well developed for several metals and chalcogenides but not yet for semiconductor metal oxides. [93][94][95] Experiments on a single-particle assembly have revealed that ordered superstructures produce a high yield of photogenerated charges and have high photoconductivity, which are difficult to achieve using traditional disordered systems consisting of crystalline nanoparticles owing to the inevitable occurrence of charge recombination at the internal interface. The Majima group used singlemolecule, single-particle fluorescence microscopy to show that photogenerated electrons could reach reactive sites over a micrometer distance and are preferentially trapped at the edge of plate-like TiO 2 MCs, in which {101} facets are predominantly exposed.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Such binary nanoparticle superstructures have been well developed for several metals and chalcogenides but not yet for semiconductor metal oxides. [93][94][95] Experiments on a single-particle assembly have revealed that ordered superstructures produce a high yield of photogenerated charges and have high photoconductivity, which are difficult to achieve using traditional disordered systems consisting of crystalline nanoparticles owing to the inevitable occurrence of charge recombination at the internal interface. The Majima group used singlemolecule, single-particle fluorescence microscopy to show that photogenerated electrons could reach reactive sites over a micrometer distance and are preferentially trapped at the edge of plate-like TiO 2 MCs, in which {101} facets are predominantly exposed.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Because of interest in the diverse properties of plasmonic nanostructures, a variety of methods have been developed to assemble them 12 into two-dimensional (2D) and threedimensional (3D) hierarchical crystalline superlattices, superparticles and superstructures, including DNA-mediated 14,[20][21][22][23] , drying-forced 24,25 , entropically driven 18,26,27 and electrostatic methods 28 . In addition, recent work on plasmonic nanoparticle clusters suggests that these structures can support magnetic dipole resonances 29,30 and Fano lineshapes 31 that are dependent on the cluster size and symmetry.…”
mentioning
confidence: 99%
“…In summary, the self-assembly of 1D NCs usually takes place under the following situations: (1) substrates driven by evaporation under external field facilitation or template, (2) interface of liquid-liquid and gas-liquid, and (3) solution through specific chemical bond. For example, Wang et al [464] reported the construction of self-assembly from the complex building blocks of CdSe-CdS core-shell nanorods. Their strategy involves the generation of water-dispersible nanorod micelles in mixing a chloroform solution and evaporation of chloroform (Fig.…”
Section: Self-assemblymentioning
confidence: 99%